Genetic mapping of escalated aggression in wild-derived mouse strain MSM/Ms: association with serotonin-related genes - Takahashi, Aki; Shiroishi, Toshihiko; Koide, Tsuyoshi (Frontiers in Neuroscience, 2014)
The Japanese wild-derived mouse strain MSM/Ms (MSM) retains a wide range of traits related to behavioral wildness, including high levels of emotionality and avoidance of humans. In this study, we observed that MSM showed a markedly higher level of aggression than the standard laboratory strain C57BL/6J. Whereas almost all MSM males showed high frequencies of attack bites and pursuit in the resident-intruder test, only a few C57BL/6J males showed aggressive behaviors, with these behaviors observed at only a low frequency. Sexually mature MSM males in their home cages killed their littermates, or sometimes female pair-mates. To study the genetic and neurobiological mechanisms that underlie the escalated aggression observed in MSM mice, we analyzed reciprocal F1 crosses and five consomic strains of MSM (Chr 4, 13, 15, X and Y) against the background of C57BL/6J. We identified two chromosomes, Chr 4 and Chr 15, which were involved in the heightened aggression observed in MSM. These chromosomes had different effects on aggression: whereas MSM Chr 15 increased agitation and initiation of aggressive events, MSM Chr 4 induced a maladaptive level of aggressive behavior. Expression analysis of mRNAs of serotonin receptors, serotonin transporter and Tph2, an enzyme involved in serotonin synthesis in seven brain areas, indicated several differences among MSM, C57BL/6J, and their consomic strains. We found that Tph2 expression in the midbrain was increased in the Chr 4 consomic strain, as well as in MSM, and that there was a strong positive genetic correlation between aggressive behavior and Tph2 expression at the mRNA level. Therefore, it is possible that increased expression of the Tph2 gene is related to escalated aggression observed in MSM.